Screening of microorganisms for chitinase production by solid-state fermentation using insect meal - Gonçalves, Ana Margarida de Matos (2020)
The use of insect meal as a new and sustainable feed ingredient has received intensive research effort, but its dietary inclusion levels are limited to its chitin content. Chitin is a complex cross-linked molecular structure, which cannot be digested by animals. To digest chitin, chemical methods may be used, presenting, however, low yield, high cost and environmental impact. Thus, the development of natural chitinases has important biological relevance, allowing it incorporation in animal feed. In this work, a screening of fungi producers of chitinase was performed in agar plates with insect meal (Hermetia illucens) and Aspergillus niger 01UAs183 had the best performance. In insect meal fermentation during 7 days, A. niger produced 50 units of chitinase per gram of dry meal. The mixture of insect meal with brewerys spent grain (1:1, w/w) fermented during 14 days lead to a 10-fold increase of chitinase activity. Mixtures of insect meal with other agro-industrial wastes are promising substrates for chitinase production, opening new strategies to improve the production of chitinase and the nutritional properties of new alternative protein sources.